Leadership competence of the barangay captains in the municipality of Sto. Tomas, Davao del Norte as perceived by barangay councilors - Canon, Patrick Henry G. (DACUN Library Committee ; Printed by TELETEXT Enterprise, 2005)
Seventy-six councilors from 19 barangays of Sto. Tomas, Davao del Norte are surveyed on their perceptions on the leadership competence of their captains in terms of adminstrative and financial management skills. Questionnaires were used to gather their responses and analyzed using mean scores and ANOVA. The captains are perceived to have high administrative and financial management skills when grouped by educational attainment and age. The same findings were observed for leadership competence. AGPerez.